ESG Regulation and Sustainability Accounting in Macroeconomic Policy: A Literature Review of Effectiveness and Challenges - Fauzi, Muhammad; Zahrolazizah, Zakkiatuz (Journal of Macroeconomics and Social Development, 2025)
This study aims to examine the effectiveness and challenges of implementing Environmental, Social, and Governance (ESG) regulations and sustainability accounting in the context of macroeconomic policy. Using the literature review method, this study collects and analyzes various scientific publications, policy reports, and global data related to ESG implementation in various countries. The results of the study indicate that ESG integration in fiscal, monetary, and investment policies can improve economic stability, strengthen global competitiveness, and encourage sustainable economic growth. However, ESG implementation also faces various obstacles, such as a lack of integration of reporting standards, greenwashing practices, limited institutional capacity, and conflicts between short-term economic goals and long-term sustainability. Therefore, efforts are needed to harmonize regulations, improve ESG literacy, and international collaboration in financing and technology transfer to optimize the role of ESG in global economic development. This study provides theoretical and practical contributions to the formulation of more inclusive and sustainable economic policies.